Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - Chapter 11 Review Problem Set - Page 520: 52



Work Step by Step

First, we use the formula: $(a+b)(a-b)=a^{2}-b^{2}$. Then, knowing that $i=\sqrt{-1}$, we can substitute $-1$ for $i^{2}$ to obtain: $(2+9i)(2-9i)$ =$(2)^{2}-(9i)^{2}$ =$4-81i^{2}$ =$4-81(-1)$ =$4+81$ =$85$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.